In situ measurement of MWA primary beam variation using ORBCOMM. (18th December 2018) - Line, J. L. B.; McKinley, B.; Rasti, J.; Bhardwaj, M.; Wayth, R. B.; Webster, R. L.; Ung, D.; Emrich, D.; Horsley, L.; Beardsley, A.; Crosse, B.; Franzen, T. M. O.; et al.
Abstract: We provide the first in situ measurements of antenna element beam shapes of the Murchison Widefield Array. Most current processing pipelines use an assumed beam shape, which can cause absolute and relative flux density errors and polarisation 'leakage'. Understanding the primary beam is then of paramount importance, especially for sensitive experiments such as a measurement of the 21-cm line from the epoch of reionisation, where the calibration requirements are so extreme that tile to tile beam variations may affect our ability to make a detection. Measuring the primary beam shape from visibilities is challenging, as multiple instrumental, atmospheric, and astrophysical factors contribute to uncertainties in the data. Building on the methods of Neben et al. [Radio Sci., 50, 614], we tap directly into the receiving elements of the telescope before any digitisation or correlation of the signal. Using ORBCOMM satellite passes we are able to produce all-sky maps for four separate tiles in the XX polarisation. We find good agreement with the beam model of Sokolowski et al. [2017, PASA, 34, e062], and clearly observe the effects of a missing dipole from a tile in one of our beam maps. We end by motivating and outlining additional on-site experiments.